Scaling BERT for Healthcare: An End-to-End Framework for Medical Document Automation - Balamurugan Sivakolunthu Vel (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article proposes a comprehensive framework for implementing BERT-based language models at scale for automated medical document processing in healthcare environments. Recent studies have demonstrated BERT models achieving accuracy rates of up to 89.7% in medical entity recognition tasks [2], suggesting significant potential for healthcare applications. The proposed architecture introduces a novel hierarchical attention mechanism specifically engineered to capture the nested complexity of medical documentation while maintaining computational efficiency in production systems. Drawing inspiration from successful implementations in pharmacy settings [15, 16], this framework features a distributed training pipeline designed to process annotated medical documents across multiple specialties, coupled with a dynamic medical vocabulary injection system that aims to preserve BERT’s contextual understanding while potentially reducing false positives in entity recognition. By leveraging distributed computing infrastructure and optimized model architecture, the framework could theoretically achieve substantial improvements over traditional approaches in both accuracy and processing efficiency, particularly in handling complex medical terminology and context-sensitive information extraction. The proposed system architecture anticipates addressing current challenges in healthcare documentation, where systems process an average of 6.2 million clinical documents annually [1]. This theoretical framework contributes to the field by proposing a scalable methodology for implementing advanced language models in healthcare settings while addressing the unique challenges of medical domain specificity and production deployment requirements.